A multi-periods offshore wind farm optimization method for supplying energy in a natural gas hydrates exploitation platform. (20th September 2021) - Wu, Xinghong; Wu, Yan; Wang, Yufei; Feng, Xiao; Chen, Guangjin
Abstract: Gas hydrates are a convenient source of clean energy for the future. The process of hydrates extraction through CO2 replacement is a promising extraction method, and methane reforming is able to produce both hydrogen and CO2 for replacement. Due to the high energy consumption of the reforming process, this work considers floating offshore wind farms as a clean energy supply source. Wind resources vary over the year and the position of floating wind turbines can be adjusted to better match wind supply in different periods. However, traditional wind farm design methods do not consider the movement of wind turbines. This work proposes a multi-period optimization based on Genetic Algorithm and Geosteiner algorithm to determine the wind turbine layout in different periods of the year. The results from the case study show that the multi-period optimization method can improve power generation by 17%, compared to a fixed wind farm layout. In addition, the results have close relation to the size of the wind farm and the frequency of adjusting the layout. Further improvements include accounting for wind turbines together with the platform energy system to increase energy efficiency. Graphical abstract: Image 1